Readmission after index hospital discharge among patients with COVID‐19: Protocol for a systematic review and meta‐analysis. Issue 4 (22nd October 2021) - AlSayegh, Abdulwahab; Gassan, Adnan A; Bajpai, Ram C.; Muller, Sara; Welsh, Victoria; Kwok, Chun Shing; Mallen, Christian D.
Abstract: Background and Aims: Hospital readmissions among COVID‐19 patients have increased the load on the healthcare systems and added more pressure to hospital capacity. This affects the ability to accommodate newly diagnosed COVID‐19 patients and other non‐COVID‐19 patients who require hospitalization. Therefore, this systematic review aims to understand the rates of and risk factors for hospital readmissions and all‐cause mortality among COVID‐19 patients who were hospitalized after being discharged following index hospitalization. Methods: Our systematic review protocol is registered with the International Prospective Register of Systematic Reviews (PROSPERO) (CRD42021232324) and prepared in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis Protocols (PRISMA‐P) 2015 statement. We will search MEDLINE (Ovid), EMBASE (Ovid), MedRxiv, Web of Science (Science Citation Index), ProQuest Coronavirus research database, Cochrane Covid‐19 study register, and WHO COVID‐19: Global literature on coronavirus disease will be identified from December 31, 2019, to May 31, 2021. Two investigators will independently screen titles and abstracts and select studies reporting hospital readmissions among COVID‐19 patients. Further, data extraction and risk of bias assessment will be carried out separately by these independent reviewers. We will extract data on demographics, readmissions, all‐cause mortality, emergency department visits, comorbidities, and factors associated with hospitalization among COVID‐19 patients. Random‐effect meta‐analysis will be performed if homogeneous groups of studies are found. The combined evidence will be further stratified according to important background characteristics if the data allow. Discussion: This systematic review will summarize the available epidemiological evidence regarding rates of hospital readmissions, comorbidities, and related factors among COVID‐19 patients who were readmitted after index hospitalization. A better understanding of the relationship between patient profiles and the rate of hospitalization will be helpful in the development of guidelines for patient management.